2006
DOI: 10.1167/iovs.05-1341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low AIPL1 Expression on Phototransduction in Rods

Abstract: Reduced AIPL1 delayed the photoresponse, decreased its amplification constant, slowed a rate-limiting step in its recovery, and limited the light-induced decrease in Ca2+. Not all changes were attributable to decreased PDE or to elevated cGMP and Ca2+ in darkness. Therefore, AIPL1 directly or indirectly affects more than one component of phototransduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
7
10
0
Order By: Relevance
“…The smaller peak amplitude was probably mostly attributable to a shorter than normal outer segment length, as we describe in detail below. The oscillations are probably the result of the shift in Ca 2ϩ sensitivity of the cyclase and hence the increase in cyclase activity; they were seen previously in recordings from L53 Y99C rods (i.e., Y99C ϩ/Ϫ ;R ϩ/ϩ ) (Makino et al, 2006), although they are larger and more consistently observed in our recent recordings from the Y99C ϩ/Ϫ ;R ϩ/Ϫ rods. Responses from G90D rods (Fig.…”
Section: ؉supporting
confidence: 72%
See 3 more Smart Citations
“…The smaller peak amplitude was probably mostly attributable to a shorter than normal outer segment length, as we describe in detail below. The oscillations are probably the result of the shift in Ca 2ϩ sensitivity of the cyclase and hence the increase in cyclase activity; they were seen previously in recordings from L53 Y99C rods (i.e., Y99C ϩ/Ϫ ;R ϩ/ϩ ) (Makino et al, 2006), although they are larger and more consistently observed in our recent recordings from the Y99C ϩ/Ϫ ;R ϩ/Ϫ rods. Responses from G90D rods (Fig.…”
Section: ؉supporting
confidence: 72%
“…Although the outer segments in the Y99C/G90D rods were Ͻ80% their normal length, even in 6-month-old animals we did not observe distortion in disk stacking (Fig. 5e) as in parental Y99C L53 mice (Makino et al, 2006). The restoration of the photoreceptor layer in Y99C/G90D mice occurred along the whole extent of the retina rather than in distinct patches (Fig.…”
Section: Camentioning
confidence: 59%
See 2 more Smart Citations
“…Of the fifteen genes known, AIPL1 is known to cause the most severe form of LCA. It encodes for essential protein required for the proper functioning of the rod photodiestrase enzyme thereby aiding proper vision [2]. The gene locus of AIPL1 is on chromosome 17p13 [3].…”
Section: Introductionmentioning
confidence: 99%